2019
DOI: 10.1016/j.jfineco.2017.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Credit default swaps and corporate innovation

Abstract: Please refer to published version for the most recent bibliographic citation information. If a published version is known of, the repository item page linked to above, will contain details on accessing it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
89
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 193 publications
(95 citation statements)
references
References 97 publications
6
89
0
Order By: Relevance
“…However, personal debts tend to be much smaller in scale than company debts; consequently, personal debts can be used to finance small business, but they will not be able to support entrepreneurship and innovation in large corporations.) Nevertheless, none of the existing studies investigate how a financial instrument facilitates debt financing in sustainable innovation investments (in a related work, Chang et al [64] investigated the relation between CDS trading and innovation and found a positive effect of CDS trading on innovation output. Our paper differs from theirs on the following aspects.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, personal debts tend to be much smaller in scale than company debts; consequently, personal debts can be used to finance small business, but they will not be able to support entrepreneurship and innovation in large corporations.) Nevertheless, none of the existing studies investigate how a financial instrument facilitates debt financing in sustainable innovation investments (in a related work, Chang et al [64] investigated the relation between CDS trading and innovation and found a positive effect of CDS trading on innovation output. Our paper differs from theirs on the following aspects.…”
Section: Discussionmentioning
confidence: 99%
“…First, our paper focuses on the debt financing of innovation and investigates how CDS trading changes the relation between debt and innovation. Debt is our explanatory variable, while in Chang et al [64], their variable of interest was CDS trading. Second, we identify a new economic channel, CEO compensation incentive, through which CDS trading facilitates the debt financing of innovation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the flip side of the same coin, the weakened monitoring by lenders can benefit shareholders if the borrowing firm can take actions that improve shareholder wealth, which were previously constrained by lender monitoring (Chang et al 2017;Campello and Matta 2012;Acharya and Ryan, 2016;Jensen and Meckling, 1976). Given their limited liability and infinite upside potential, shareholders' equity is synonymous with a call option with face-value of debt as the strike price.…”
Section: Introductionmentioning
confidence: 99%